Role of blue‐light cystoscopy in detecting invasive bladder tumours: data from a multi‐institutional registry. (26th October 2021) - Ahmadi, Hamed; Ladi‐Seyedian, Seyedeh Sanam; Konety, Badrinath; Pohar, Kamal; Holzbeierlein, Jeffrey M.; Kates, Max; Willard, Brian; Taylor, Jennifer M.; Liao, Joseph C.; Kaimakliotis, Hristos Z.; Porten, Sima P.; Steinberg, Gary D.; et al.
Abstract : Objectives: To evaluate the role of blue‐light cystoscopy (BLC) in detecting invasive tumours that were not visible on white‐light cystoscopy (WLC). Patients and Methods: Using the multi‐institutional Cysview registry database, patients who had at least one white‐light negative (WL–)/blue‐light positive (BL+) lesion with invasive pathology (≥T1) as highest stage tumour were identified. All WL–/BL+ lesions and all invasive tumours in the database were used as denominators. Relevant baseline and outcome data were collected. Results: Of the 3514 lesions (1257 unique patients), 818 (23.2%) lesions were WL−/BL+, of those, 55 (7%) lesions were invasive (48 T1, seven T2; 47 unique patients) including 28/55 (51%) de novo invasive lesions (26 unique patients). In all, 21/47 (45%) patients had WL−/BL+ concommitant carcinoma in situ and/or another T1 lesions. Of 22 patients with a WL−/BL+ lesion who underwent radical cystectomy (RC), high‐risk pathological features leading to RC was only visible on BLC in 18 (82%) patients. At time of RC, 11/22 (50%) patients had pathological upstaging including four (18%) with node‐positive disease. Conclusions: A considerable proportion of invasive lesions are only detectable by BLC and the rate of pathological upstaging is significant. Our present findings suggest an additional benefit of BLC in the detection of invasive bladder tumours that has implications for treatment approach.